2018
DOI: 10.1016/j.dadm.2018.07.004
|View full text |Cite
|
Sign up to set email alerts
|

Machine learning of neuroimaging for assisted diagnosis of cognitive impairment and dementia: A systematic review

Abstract: Introduction Advanced machine learning methods might help to identify dementia risk from neuroimaging, but their accuracy to date is unclear. Methods We systematically reviewed the literature, 2006 to late 2016, for machine learning studies differentiating healthy aging from dementia of various types, assessing study quality, and comparing accuracy at different disease boundaries. Results Of 111 relevant studies, most assessed Alzheimer's dis… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

4
208
1
2

Year Published

2018
2018
2023
2023

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 216 publications
(215 citation statements)
references
References 30 publications
4
208
1
2
Order By: Relevance
“…This might make them better suited to detect associations between variables than logistic or Cox regression [11]. However, as discussed by Pellegrini et al [8], in a published systematic literature and meta-analyses of machine learning techniques in neuroimaging for cognitive impairment and dementia, studies using machine learning algorithms also show limitations. Generalizability of results generated from the application of these techniques and their transfer to clinical use are likely to be constrained because of their over-reliance on one data source, the fact that they commonly use data from populations with greater proportions of cases (i.e., individuals with the diseases) and lower proportions of control subjects, they are usually derived using only one machine learning method and the application of varying validation methods [7,8].…”
Section: Machine Learningmentioning
confidence: 99%
“…This might make them better suited to detect associations between variables than logistic or Cox regression [11]. However, as discussed by Pellegrini et al [8], in a published systematic literature and meta-analyses of machine learning techniques in neuroimaging for cognitive impairment and dementia, studies using machine learning algorithms also show limitations. Generalizability of results generated from the application of these techniques and their transfer to clinical use are likely to be constrained because of their over-reliance on one data source, the fact that they commonly use data from populations with greater proportions of cases (i.e., individuals with the diseases) and lower proportions of control subjects, they are usually derived using only one machine learning method and the application of varying validation methods [7,8].…”
Section: Machine Learningmentioning
confidence: 99%
“…Similar trends have also been observed in the analytics space where AI including sophisticated Machine Learning (ML) algorithms and frameworks such as deep learning continue to be developed and improved. A systematic review by Pellegrini et al [19] found over 110 publications on various initiatives where ML approaches have been employed to develop prediction models for cognitive impairment and AD using neuroimaging data. These research efforts are being extended to other data sources and domains such as linguistic analysis of text messages; speech analysis [20,21]; and also through the human eyes using retinal imaging [22] with promising results.…”
Section: Dementia Early Intervention Through Big Data and Ai In Lmicmentioning
confidence: 99%
“…Comparative evaluations were presented in [35], the authors presented a literature review of machine learning techniques used for AD detection. Their work illustrates the quality assessment of the previous studies and a comparison of the details.…”
Section: Literature Reviewmentioning
confidence: 99%